SUBSTANTIAL CHANGES IN CARDIOVASCULAR HEALTH OCCUR FROM ADOLESCENCE TO EMERGING ADULTHOOD. (April 2021) - Park, Chloe; Taylor, Hannah; Rapala, Alicja; Williams, Suzanne; Jones, Siana; Howe, Laura; Chaturvedi, Nish; Hughes, Alun
Abstract : Objective: 17–24 years is a distinct period of lifestyle change. However little is known regarding changes in cardiovascular (CV) health during this time. We explored changes in Left ventricle (LV) structure and function, arterial stiffness, compliance and resistance in a large population-based birth cohort and investigated associations with body composition, haemodynamics and lifestyle choices. Figure. No caption available. Design and method: 724 participants had repeated echocardiography, blood pressure (BP) and body composition (using DEXA) measures aged 17y and 24y. Change in key outcomes and exposures from 17–24y were derived. Principal Component Analysis (PCA) was applied to reduce intercorrelated exposures into groups of independent factors. Principal Component (PC) 1: contained factors relating to change in blood pressure, PC2: change in body size (body mass index, fat mass and lean mass), and PC3: lifestyle (smoking and alcohol)). Linear regression assessed associations between PCs and change in CV outcomes. Results: From 17–24y systolic BP, pulse pressure and alcohol use decreased. All other exposures increased (Table). Indexed LV mass (LVMI) and systolic function (cardiac output (CO), Tissue Doppler peak S) increased, while diastolic function declined (Mitral E:e'). Pulse wave velocity (PWV) and compliance (TAC) increased, peripheral resistance (TPR) decreased. In age and sex adjusted regression analysis PC2 had the strongest association with all LV changes. Vascular changes (PWV, TPR) were most strongly associated with PC1. While PC3 showed the weakest associations. All associations remained after further adjustment for socioeconomic status, birth weight and education Conclusions: Substantial CV changes occur from adolescence to emerging adulthood. Changes in body size and composition have a considerable effect on LV structure and function, while changes in vascular health are associated with changing haemodynamics. These results imply that despite being relatively early in the life-course, this is an important time to control CV risk factors to improve future CV health.